Meningkatan Keterampilan Membaca Aksara Jawa Melalui Model Quantum Learning Berbantuan Media MONORAJA - Kusuma, Hesti Maesa; Istiningsih, Galih; Wardana, Aditia Eska; Rahmawati, Puji (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The aim of this research is to help fourth grade students at SD Negeri Pucung read Javanese script more fluently by utilizing the Quantum Learning learning paradigm with support from MONORAJA. The repeated cycle (spiral) model known as the Kemmis Tanggart design was used in this Classroom Action Research study. Fourth grade students and teachers at Pucung State Elementary School were used as research subjects. A performance test approach was used in collecting research data. The research findings can be seen from the increase in the average pre-action score for class IV students from 63.52 in reading Javanese script to 69.88 in cycle I and then to 79.94 in cycle II after improvements were made. In cycle I, the percentage of students who completed the KKM and entered the Very Good (A) category increased from 41% to 76%, and in cycle II it became 88%. Observation results show that when students use the Quntum Learning learning model with the help of Monopoly Javanese script, student engagement in class increases, students are more enthusiastic about learning, students become more confident, students answer questions and ask questions, and they enjoy learning.